Decision Support System for Wedding Package Using Multi-Objective Optimization of Ratio Analysis Method - Indah Fitri Astuti; Awang Harsa Kridalaksana; Rasni Alex; Dewi Fitri; Dedy Cahyadi; Aulia Khoirunnita (TEPIAN, 2024)
Some   of the problems in preparing a wedding day are determining the venue, event concept, concept and others are very time-consuming. Wedding organizers are an option to overcome these problems; one of the wedding organizers in Samarinda is Galeri Shella, which has various wedding packages with facilities and prices, making it difficult for brides-to-be. To make it easier to make the right wedding package decision, a decision support system is made. The decision aims to provide wedding package recommendations with criteria that can be chosen by the bride and groom and their budget. The method used in this system is Multi-Objective Optimization of Ratio Analysis (MOORA) using six criteria catering, venue, decoration, documentation, makeup and price, as a reference calculation that can produce the best wedding package recommendations according to the wishes of the bride and groom. The research results show that the system functions well, is easy to use, and makes it easier for brides to choose wedding packages. From the results of accuracy testing, it is known that the results of manual calculations and the system make no difference, and this study obtained an accuracy value of 100%.